2002
DOI: 10.1097/00002030-200212003-00007
|View full text |Cite
|
Sign up to set email alerts
|

Mobile populations and HIV/AIDS in Central America and Mexico: research for action

Abstract: Given the conditions that exist in these transit stations, interventions should be multisectoral, sustainable, and should defend the human rights of various groups, including women and people living with HIV/AIDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
0
12

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 3 publications
1
60
0
12
Order By: Relevance
“…In Peru and in most settings with concentrated epidemics, high-risk groups have generally been limited to female sex workers or to special male groups (e.g. gay men, truck drivers, migrants, inmates) (Bronfman et al 2002;Gysels et al 2001;Homaifar and Wasik 2005;Kyrychenko and Polonets 2005;Mills et al 2001;Simooya et al 2001). In this study, two non-traditional high-risk groups, the esquineros and movidas were characterized after their identification through formative ethnographic work (Rosasco et al 2004;Salazar et al 2005).…”
Section: Discussionmentioning
confidence: 97%
“…In Peru and in most settings with concentrated epidemics, high-risk groups have generally been limited to female sex workers or to special male groups (e.g. gay men, truck drivers, migrants, inmates) (Bronfman et al 2002;Gysels et al 2001;Homaifar and Wasik 2005;Kyrychenko and Polonets 2005;Mills et al 2001;Simooya et al 2001). In this study, two non-traditional high-risk groups, the esquineros and movidas were characterized after their identification through formative ethnographic work (Rosasco et al 2004;Salazar et al 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Women is this subgroup may engage in sex against their will and condom negotiation may less possible [47]. In this study, we defined FSWs broadly as transaction in which money, goods, drugs or alcohol were exchanged for a sexual service.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, limited studies in immigrant FSW populations have revealed positive behavioral changes in condom use for vaginal and anal sex among Asian FSW in Sydney (Pell et al 2006) and consistent condom use among Latin American FSW in Madrid (Belza et al 2004). However, HIV sexual risk behaviors and lack of knowledge regarding HIV/AIDS and its route of transmission were observed among migrant workers in Central America and Mexico (Bronfman et al 2002), China (Bandyopadhyay and Thomas 2002) as well as in northeastern Brazil (Kerr-Pontes et al 2004).…”
Section: Introductionmentioning
confidence: 99%